Response of striosomal opioid signaling to dopamine depletion in 6-hydroxydopamine-lesioned rat model of Parkinson's disease: a potential compensatory role - Koizumi, Hidetaka; Morigaki, Ryoma; Okita, Shinya; Nagahiro, Shinji; Kaji, Ryuji; Nakagawa, Masanori; Goto, Satoshi (Frontiers in Cellular Neuroscience, 2013)
The opioid peptide receptors consist of three major subclasses, namely, μ, δ, and κ (MOR, DOR, and KOR, respectively). They are involved in the regulation of striatal dopamine functions, and increased opioid transmissions are thought to play a compensatory role in altered functions of the basal ganglia in Parkinson's disease (PD). In this study, we used an immunohistochemistry with tyramide signal amplification (TSA) protocols to determine the distributional patterns of opioid receptors in the striosome-matrix systems of the rat striatum. As a most striking feature of striatal opioid anatomy, MORs are highly enriched in the striosomes and subcallosal streak. We also found that DORs are localized in a mosaic pattern in the dorsal striatum (caudate-putamen), with heightened labeling for DOR in the striosomes relative to the matrix compartment. In the 6-hydroxydopamine-lesioned rat model of PD, lesions of the nigrostriatal pathways caused a significant reduction of striatal labeling for both the MOR and DOR in the striosomes, but not in the matrix compartment. Our results suggest that the activities of the striosome and matrix compartments are differentially regulated by the opioid signals involving the MORs and DORs, and that the striosomes may be more responsive to opioid peptides (e.g., enkephalin) than the matrix compartment. Based on a model in which the striosome compartment regulates the striatal activity, we propose a potent compensatory role of striosomal opioid signaling under the conditions of the striatal dopamine depletion that occurs in PD.